A virtual reality intervention to reduce death anxiety and stress in adults: examining the effect of a near-death experience simulation - Khandan, Parya; Ennemoser, Benjamin; Foster, Ryan D.; Dubose, Logan; Lu, Zhipeng (Frontiers in Virtual Reality, 2025)
Death anxiety (DA) and stress pose significant psychological challenges that negatively impact health and wellbeing. Exposure therapy—a behavioral approach that reduces fear by repeatedly and safely exposing individuals to feared stimuli—has demonstrated effectiveness in treating anxiety. However, traditional exposure methods are limited in addressing DA, as individuals cannot authentically experience death. This study examined the efficacy of an immersive virtual reality (VR) near-death experience (NDE) simulation as an alternative to an actual NDE for reducing DA and stress. Sixty-one adults engaged in a first-person VR NDE experience, randomized to either a narrated or non-narrated version. Pre- and post-intervention questionnaire comparisons revealed significant reductions in both DA and stress, with no significant differences between the two versions. These findings contribute to the growing evidence on how immersive VR can modulate emotional and cognitive responses related to mortality, supporting its potential as a scalable tool for psychological interventions and fostering behavioral changes such as reduced avoidance of death-related thoughts, greater resilience, and shifts toward more positive, value-driven living.